Combining Ability Analysis of Newly Developed Male Sterile Lines of Pearl Millet - Yadav, H P; Sabharwal, P S (Annals of Arid Zone, 2016)
Seven newly developed male sterile lines and eleven advanced inbreds of pearl millet (Pelllzisetu111 glallc1I111) were crossed in a line x tester fashion at Haryana Agricultural University, Hisar, to develop 77 single cross hybrids. The combining ability analysis revealed the significance of lines, testers and lines x testers, indicating the presence of diversity in parents and hybrids as well. The preponderance of non-additive component for grain yield and that of additive for days to 50% tlowering and earhead length was observed. Estimates of GCA effects revealed that among' females (lines) ICMS 93111 A, followed by ICMS 92777 A were good general combiners for grain yield and earhead length. ICMS 94222A was top general combiner for earliness, followed by ICMS 95444A. Among the male (testers) parents the good combiners were ICR 161, CSSC 46-2, HTP 91/32 for grain yield, H 90/4-5, H 77/371, H 77/29-2 and IH 8 for earliness and CSSC 46-2 and HTP 91/34 for earhead length.